Respuesta :
Notice that 216 is a perfect cube and so is 125.
You have the sum of two cubes which is factorable and follows the pattern:
[tex] a^3 + b^3 = (a + b)(a^2 - ab + b^2) [/tex]
[tex] 216p^3 + 125q^3 = [/tex]
[tex] = (6p)^3 + (5q)^3 [/tex]
[tex] = (6p + 5q)(36p^2 - 30pq + 25q^2) [/tex]
You have the sum of two cubes which is factorable and follows the pattern:
[tex] a^3 + b^3 = (a + b)(a^2 - ab + b^2) [/tex]
[tex] 216p^3 + 125q^3 = [/tex]
[tex] = (6p)^3 + (5q)^3 [/tex]
[tex] = (6p + 5q)(36p^2 - 30pq + 25q^2) [/tex]
Factored form involves factors who multiply themselves to make that expression or value.
The factored form of given expression is [tex](6p+5q)(36p^2 - 30pq + 25q^2)[/tex]
Given that:
- The expression: [tex]216p^3+125q^3[/tex]
To find:
The factored form of given expression.
Using the identity [tex]a^3 + b^3 = (a+b)(a^2 - ab + b^2)[/tex]:
Since [tex]a^3 + b^3 = (a+b)(a^2 - ab + b^2)[/tex] , and
since [tex]216p^3+125q^3 = (6p)^3 + (5q)^3[/tex]
Thus:
[tex]\begin{aligned}216p^3+125q^3 &= (6p)^3 + (5q)^3\\ &= (6p + 5q)((6p)^2 - (6p)(5q) + (5q)^2))\\ &=(6p+5q)(36p^2 - 30pq + 25q^2) \end{aligned}[/tex]
Thus, the factored form of given expression is [tex](6p+5q)(36p^2 - 30pq + 25q^2)[/tex]
Learn more about factored form here:
https://brainly.com/question/43919